The relationship between zinc and hepatic steatosis - Dikker, Okan; Dağ, Hüseyin; Türkkan, Emine; Çetin Dağ, Nevin; Çakar, Nafiye Emel (Journal of Surgery and Medicine, 2019)
Nonalcoholic fatty liver disease (NAFLD) is the most commonly diagnosed liver disease in the recent years, with a prevalence of 15-20% among normal population. Liver steatosis is also a complication of obesity and affects 22-52% of obese children. In this aspect, it is an important public health problem. Increases in the amount of fatty acids entering the liver, increase in fatty acid synthesis and disorders in its secretion are included in its pathogenesis. The relationship between zinc, which is the second most abundant trace element found in the body after iron and necessary for many enzymes to function properly, and fatty liver disease has been shown in previous studies. The aim of this review is to discuss the relationship between zinc and liver steatosis in the light of current studies and contribute to the literature.